If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5g + 74 = 12g + 11 Reorder the terms: 74 + 5g = 12g + 11 Reorder the terms: 74 + 5g = 11 + 12g Solving 74 + 5g = 11 + 12g Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-12g' to each side of the equation. 74 + 5g + -12g = 11 + 12g + -12g Combine like terms: 5g + -12g = -7g 74 + -7g = 11 + 12g + -12g Combine like terms: 12g + -12g = 0 74 + -7g = 11 + 0 74 + -7g = 11 Add '-74' to each side of the equation. 74 + -74 + -7g = 11 + -74 Combine like terms: 74 + -74 = 0 0 + -7g = 11 + -74 -7g = 11 + -74 Combine like terms: 11 + -74 = -63 -7g = -63 Divide each side by '-7'. g = 9 Simplifying g = 9
| 7x+3=-7+4x+16 | | 5=3-2 | | -7(-2x+5)=-203 | | -3/110+2 | | 3/5*-1/22 | | 5x+10=82-4 | | 0.35-2.95=0.5(x-5) | | (3)/4(x-1)=x-3 | | 12x+50= | | 5(V+2)-8V=25 | | -3*-15/2 | | (9-8)8= | | f(x)=260 | | 3v+19=5v-5 | | 1(p)=8 | | 6x+41=-37 | | 12x^3+16x^2-5x-3=0 | | -5/2*3 | | -9x-45=18 | | c+13=6c+8 | | -3x+6=20 | | -4/3*3 | | 0.15-3.25=0.4(x-5) | | -5/22+11/5 | | -5x+15=-55 | | j-2(1-2j)=(39j-3)+5 | | 3x+x^2=-x+3 | | -2=-2y | | 5*-1/22 | | 3x+x^2=-1x+3 | | -21+5x=-76 | | -(4y+1)-(-3y-4)=-3 |